Chapter Emerging Photovoltaic Technologies and Eco-Design-Criticisms and Potential Improvements - Barolo, Claudia (InTechOpen, 2020)
An efficient waste management for emerging photovoltaic (PV) technologies is not mature yet. The problematic aspects along with the possible failure's identification have a pivotal role in modelling the future end-of-life management strategies. The identification of substances of concern (e.g. high cost, low availability, and high toxicity) and valuable materials is a key point to better define the research priorities to improve the eco-design of these technologies. The ultimate goal is to promote the disposal processes which enhance the repair, refurbishment, and recover opportunities and so the profitability of recycling. These studies can also prompt the investigation of innovative materials which are more cost-effective and/or coming from renewable resources or secondary raw materials. Forecasting the waste management technologies for the emerging photovoltaics is highly challenging. In this context, our purpose is to provide an overview of the critical elements and understand the appropriate corrective improvements towards more sustainable technologies.